2019
DOI: 10.1101/737361
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geomagnetic field absence reduces adult body weight of a migratory insect by disrupting feeding behavior and appetite regulation

Abstract: The geomagnetic field (GMF) is well documented for its essential role as a cue used in animal orientation or navigation. Recent evidence indicates that the absence of GMF can trigger stress-like responses such as reduced body weight, as we have previously shown in newly emerged adults of the brown planthopper, Nilaparvata lugens. To test the hypothesis that reduced feeding in the absence of the GMF leads to a decrease of N. lugens body weight, we compared magnetic responses in feeding behavior, glucose levels,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The brown planthopper, N. lugens , is one of the most important rice pests in Asia, which has the ability of magnetic response due to the magnetic particles in its abdomen (Chapman et al ., 2011; Xie et al ., 2011; Yan et al ., 2015; Pan et al ., 2016; Wan et al ., 2020, 2021). Recently, research based on the physiological magnetic response of N. lugens found that the deletion of the magnetic receptor protein (MagR/IscA1) significantly shortened the life span of brachypterous female adults, providing a new strategy for the control of N. lugens (He et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The brown planthopper, N. lugens , is one of the most important rice pests in Asia, which has the ability of magnetic response due to the magnetic particles in its abdomen (Chapman et al ., 2011; Xie et al ., 2011; Yan et al ., 2015; Pan et al ., 2016; Wan et al ., 2020, 2021). Recently, research based on the physiological magnetic response of N. lugens found that the deletion of the magnetic receptor protein (MagR/IscA1) significantly shortened the life span of brachypterous female adults, providing a new strategy for the control of N. lugens (He et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The needed primers for qRT‐PCR were designed using the Primer Premier 5.0 software, which were provided in Table S2 with effectiveness analysis. RPL5 and 18S were used as the internal standard (Wan et al ., 2021). The qRT‐PCR procedure was as follows: 95 °C for 30 s; then 40 cycles of 95 °C for 5 s and 60 °C for 34 s. The results of qRT‐PCR were determined using the 2 −ΔΔCT method (Livak and Schmittgen, 2001).…”
Section: Experiments Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the expression of putative magnetosensors, CRY1 and CRY2 , in the early developmental stage of the white‐backed planthopper is altered in HMF, suggesting that cryptochromes are located in the upstream of magnetic response [Wan et al, 2015]. Additionally, HMF exposure reduces the body mass of brown planthoppers by disrupting their feeding behavior, which is caused by elevated glucose levels [Wan et al, 2021]. Moreover, it is remarkable that even tardigrades (or water bears), which are known for their tenacious vitality, exhibit a lower survivability rate while entering anhydrobiosis in an anhydrobiotic state, and return to the active state after HMF exposure [Erdmann et al, 2021].…”
Section: The Biological Effects Of Hmfmentioning
confidence: 99%
“…Notably, cosmic radiation causes the accumulation of ROS, and the combined effects of HMF and radiation on ROS is an issue to be further studied. In contrast, HMF can reduce aerobic metabolism, as observed in mouse skeletal muscle cells [Fu et al, 2016], and is also associated with the accumulation of blood glucose in insects and citric acid in mouse muscle tissue [Hu et al, 2020; Wan et al, 2021]. However, a 72 h treatment of human spermatozoa promotes glucose consumption instead of accumulation [Truta et al, 2012].…”
Section: Mechanisms Of Hmf Biological Effectsmentioning
confidence: 99%